2019
DOI: 10.1142/s0218271819501529
|View full text |Cite
|
Sign up to set email alerts
|

An interacting new holographic dark energy model: Observational constraints

Abstract: In this paper, we study the interacting DGP braneworld Holographic Dark Energy model in a spatially flat FRW universe. Mainly, in this study we concentrate our attention on both interacting and non-interacting form of the model. The study shows that the equation of state and the deceleration parameter depict an accelerated universe for all variety of interactions. On the other hand, the StateFinder analysis shows that of the interacting and non-interacting behave similar to both quintessence and phantom dark e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 91 publications
1
10
0
Order By: Relevance
“…Finally, it is important to mention that holographic models for dark energy are supported by the observational data and exhibit a consistent matter growth perturbations and stability [7,23,32,43].…”
Section: Final Remarksmentioning
confidence: 60%
See 1 more Smart Citation
“…Finally, it is important to mention that holographic models for dark energy are supported by the observational data and exhibit a consistent matter growth perturbations and stability [7,23,32,43].…”
Section: Final Remarksmentioning
confidence: 60%
“…See also Ref. [43], where was found that the interacting scheme for holographic dark energy evolves in agreement with observational data and exhibits stability, and Ref. [44], where the inclusion of spatial curvature in the interacting scheme leads to an expanding and accelerating universe.…”
Section: B Interacting Cosmological Fluidsmentioning
confidence: 63%
“…The interaction term proportional to the DE density or to the DM density or to a linear combination of both densities was well studied in literature [52,53,54,55]. But in some literature [39,40,56,57,37,58] the non linear interaction i.e., an interaction proportional to the product of DM density and DE energy density were studied and found to be favored observationally than linear interaction between dark sectors [41]. The general form for the nonlinear interaction can be written as [39],…”
Section: The Model : Holographic Ricci De As Running Vacuum With Nonl...mentioning
confidence: 99%
“…Interacting holographic dark energy models are discussed in Ref. [20]. Models of future singularities are classified in Ref.…”
Section: Introductionmentioning
confidence: 99%